2-Deoxy D-Glucose in COVID-19: Current Research Trends - Robinson, Jared; Banerjee, Indrajit; Leclézio, Alexandra (Journal of College of Medical Sciences-Nepal, 2022)
2-Deoxy D- glucose is a novel drug. It is an analogue of glucose which has innate therapeutic uses due to both its antiviral properties as well as its anti-neoplastic action. The SARS-CoV-2 virus binds to the host cell via the (S2) spike glycoprotein. Once viral entry has been gained into the host cell the virus hijacks the host’s intracellular machinery via 2 factors; 3CLpro and NSP15. It has been shown through the use of Toxicity estimation software as well as via Molinspiration that 2-Deoxy D- glucose and its aforementioned isomers can effectively bind with 3CLpro and NSP15 and intern thus immobilize the SARS-CoV-2 virus via the incapacitation of its viral receptors. On a molecular level the 2-Deoxy D- glucose derivatives produce a H bond with the glutamine AA residues of the SARS-CoV-2 (S2) spike, as well form a Hydrogen bond with the 2 Deoxy D-glucose and proline residues of the SARS-CoV-2 protease. It is thus evident via both molecular and in silico studies that 2 Deoxy D- glucose and its isomers have the ability to offer further protection and or have imperative diminution capabilities in the treatment of patients with the COVID-19 infection. 2-Deoxy D- glucose has shown promising results in clinical trials and has produced faster recovery in hospitalized patients and abridged additional oxygen dependence in COVID-19 patients in various states across India. The scope and potential for the use of 2-Deoxy D- glucose in the treatment of COVID-19 is evident. It is therefore of great importance that further in vivo studies are conducted with 2-Deoxy D-glucose in order to expedite the process of bringing this potentially lifesaving drug to market.